Does international outsourcing really lower workers' income? - Erkki Koskela; Jan König (Institute for the Study of Labor (IZA), 2010)
We analyze the impact of international outsourcing on income, if the domestic labor market is imperfect. We distinguish in our analysis between the case where the parties negotiate over the wage only and where they negotiate over both wage and profit share. We find that in the first case outsourcing will reduce (increase) workers' income, if the labor union's bargaining power is sufficiently high (low) and outsourcing will increase workers' income in the second case. For the amount of optimal international outsourcing, we find that it is in a pure wage bargaining system positively (negatively) affected by a sufficiently high (low) labor union's bargaining power, while in a wage and profit share bargaining system, a higher union's bargaining power decreases the optimal amount of outsourcing.
Keywords: E23; E24; J23; J33; J82; 330; Strategic outsourcing; profit sharing; labor market imperfection; Offshoring; Auslandsproduktion; Verteilungswirkung; Erfolgsbeteiligung; Lohnverhandlungen; Tarifpolitik; Theorie